The Perpetuation of Lazy Thinking by Exploiting Writing Artificial Intelligence Tools: Perceptions from Students in the University of Limpopo - Selelo, Mohale Ernest (JEET, Journal of English Education and Technology, 2024)
The advent of technological innovation systems has raised concerns about the quality of education. This paper aims to examine and critique the prevalence of lazy thinking and writing among students who rely on online tools during their academic pursuits. It argues that the use of artificial writing software by students not only undermines their intellectual capabilities but also poses a threat to the overall standard of education. Consequently, the emergence of various virtual tools, including ChatGBT, jenni.ai, Calmly writer, living writer, Hubspot’s Blog Topic Generator, The CoSchedule headline analyzer app, Portent’s Idea Generator, Scrivener, and Hemingway Editor, has become prevalent among students in their educational journey. Acknowledging that technology's progress cannot be halted, it becomes crucial to ensure that such advancements does not replace the essence of creative thinking and writing within academic environments. This conceptual study, employing a qualitative and quantitative approach, explores this concern. The research gathers insights from students at the University of Limpopo on the matter in question. The findings indicate that a significant number of students resort to online software due to laziness, shortsightedness, and a lack of creativity when completing academic assessments. Despite the university's implementation of Turnitin, students still manage to bypass the system using these online tools. Consequently, the study highlights the susceptibility of the quality of education to the influence of online writing software. This paper recommends two key alternatives: firstly, the adoption of Activated Classroom Teaching and secondly, the encouragement of ‘Socratic Method’ of teaching and learning to encourage active and radical thinking amongst students and improve the quality of education.